Character Selection and Tolerance Screening Efectivity on Static Hydroponic Method Under Drought Stress in Rice - N. Nasaruddin; Muh Farid Bdr; Yunus Musa; Hari Iswoyo; muhammad Fuad Anshori; Andi Isti Sakinah; Muh. Arifuddin; Adinda Asri Laraswati; Ardian Reski Handayani (Universitas Sembilanbelas November Kolaka, 2020)
This research was aimed to evaluate the efectivity of screening method and identification of tolerance screening selection character in statis hydroponic system towards drough stress. The research was carried out in Hydroponic Screenhouse Perdos Unhas, Tamalanrea, Makassar which throughout February-April 2020. This research was conducted in factorial design in nested patterns, where environment was the nested replication. Environments used were normal (0% PEG) and drought stress (10% PEG). Five rice varieties were used: Inpari 34, Ciherang, IR29 and Jeliteng. Research result showed that canopy height and fresh weight were the suitable selection character in drought tolerance screening through statis hydroponic cultivation. Grouping consistency was found between drought and salinity stress. Inpari 34, Ciherang, Jeliteng and Inpari 29 was considered to be have drought tolerance, whilst IR29 was examined to be responsive to drough stress in hydroponic culture. From the overall result, it can be concluded that hydroponic screening and PEG application was quite effective in rice drought stress tolerance screening